Sludge reduction technologies in wastewater treatment plants - Foladori, Paola (IWA Publishing, 2010)
This book is a review of the sludge reduction techniques integrated in wastewater treatment plants with detailed chapters on the most promising and most widespread techniques. The aim of the book is to update the international community on the current status of knowledge and techniques in the field of sludge reduction.